2020
DOI: 10.3389/fphar.2020.583311
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Oral Anticoagulants in Older Patients With Atrial Fibrillation: A Systematic Review and Meta-Analysis

Abstract: Background and Objective: Atrial fibrillation (AF), the most common cardiac arrhythmia, typically increases with age. Oral anticoagulants (OACs) are the cornerstone of treatment to reduce the associated risk for systemic thromboembolism. Four large randomized controlled trials (RCTs) have shown that non-vitamin K antagonist oral anticoagulants (NOACs) are non-inferior to vitamin K antagonists (VKAs) in preventing stroke and systemic embolism, as well as regarding their risk for major bleeding. However, as vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 96 publications
1
79
1
5
Order By: Relevance
“…Consideration of the modified Frailty index, 93-95 comorbidities, 96 and current medications including anticoagulants is important for reducing morbidity and hospital length of stay. 97,98 Multiple levels of ACDF or corpectomies in older individuals can be complicated by dysphagia and swallowing difficulty. [99][100][101][102][103] The most important imaging biological marker of tCSCI is the intramedullary lesion -the product of kinetic energy and molecular cascades immediately following trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consideration of the modified Frailty index, 93-95 comorbidities, 96 and current medications including anticoagulants is important for reducing morbidity and hospital length of stay. 97,98 Multiple levels of ACDF or corpectomies in older individuals can be complicated by dysphagia and swallowing difficulty. [99][100][101][102][103] The most important imaging biological marker of tCSCI is the intramedullary lesion -the product of kinetic energy and molecular cascades immediately following trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of the modified Frailty Index, 89–92 comorbidities, 92 and current medications including anticoagulants is important for reducing morbidity and hospital length of stay. 93 , 94 Multiple levels of ACDF or corpectomies in older individuals can be complicated by dysphagia and swallowing difficulty. 95–99 …”
Section: Discussionmentioning
confidence: 99%
“…To explore this heterogeneity, we performed post-hoc subgroup analyses. We decided to stratify the analyses according to agent because previous systematic reviews and large real-world studies had suggested that dabigatran and rivaroxaban tend to have a higher bleeding risk than apixaban and edoxaban [13,15,16,18,20,54].…”
Section: Major or Clinically Relevant Bleedingmentioning
confidence: 99%
“…Alongside these two classes, antiplatelet agents are also prescribed despite not being recommended for stroke prevention in AF patients, regardless of stroke risks (11). In a recent meta-analysis in older AF patients, NOACs were associated with superior e cacy in preventing stroke/systemic embolism (HR 0.83, 95% CI: 0.74-0.94) and non-inferiority safety for major bleeding (HR 0.93, 95% CI: 0.86-1.01), intracranial bleeding (HR 0.58, 95% CI: 0.50-0.67) and gastrointestinal bleeding (HR 1.17, 95% CI: 0.99-1.38) compared to VKAs (12). Due to the perceived risks of bleeding, many patients are not offered anticoagulants, particularly patients at risk of falls or with history of falls.…”
Section: Systematic Review Registrationmentioning
confidence: 99%